Kemampuan Komunikasi Matematis Siswa dalam Menyelesaikan Soal Materi Komposisi Fungsi Ditinjau dari Kemampuan Matematika - Lutfianannisak Lutfianannisak; Ummu Sholihah (Jurnal Tadris Matematika, 2018)
Mathematical communication is the way students express mathematical ideas either orally, written, drawing/diagrams, presenting in algebraic form, or using mathematical symbols. This research is motivated by field fact that shows that the learning process in school has not given opportunity to students to communicate idea related to their understanding. In this case the authors analyze the mathematical communication skills of X-IPA MA superior students Jabal Noor Trenggalek use the indicators on mathematical communication by selecting the subject by purposive sampling as much as 6 students of X-IPA class academic year 2016/2017 high-ability, average, and low. The purpose of this study is to describe the mathematical communication ability of the X-IPA MA superior students of Jabal Noor Trenggalek in solving the mathematical problems of the composition of functional material in terms of mathematical ability. This research uses qualitative approach with descriptive research type. Data were collected by giving tests and interviews. Data analysis is done through data reduction, data presentation, and conclusion. The results showed that the mathematical communication ability of high, medium, and low-ability students fulfilled the 3 components of communication standards established by NCTM, namely: 1) organizing and consolidating their mathematical thinking through communication; 2) analyzing and evaluating mathematical thinking (mathematical thinking) and strategies used by others, 3) using mathematical language to express mathematical ideas correctly.